Kemampuan Reprensentasi Visual Mahasiswa PGSD Pada Mata Kuliah Statistik Pendidikan - Sugiyono, Sugiyono (LPPM Press, 2023)
This study aims to analyze the visual representation abilities of students of the Elementary School Teacher Education study program in presenting data in the Education Statistics course. This research is a qualitative descriptive study with research subjects being students of the Elementary School Teacher Education study program at STKIP PGRI Pacitan. Data was collected from the results of student answers in making tables, pie charts and bar charts. Data analysis uses an interactive analysis model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the students' visual representation abilities in making frequency distribution tables using either computer applications or manual drawing meet the visual representation indicators. In illustrating a pie chart using a computer application it fulfills the indicators of visual representation, while students who draw manually do not fulfill the indicators. And in illustrating bar charts using computer applications it does not meet the indicators, while students who draw manually meet the visual representation indicators.